2009
DOI: 10.1080/01421590903095502
|View full text |Cite
|
Sign up to set email alerts
|

Web-based collaborative training of clinical reasoning: A randomized trial

Abstract: Background: Clinical reasoning skills are essential for medical practice. Problem-based collaborative learning via the internet might prove useful in imparting these skills. Aim: This randomized study assessed whether web-based learning (WBL) is superior to face-to-face problem-based learning (PBL) in the setting of a 6-week cardio-respiratory course. Methods: During winter term 2007/08, all 148 fourth-year medical students enrolled in the 6-week course consented to be randomized in small groups to diagnose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 31 publications
2
46
1
Order By: Relevance
“…A blog created to teach clinical reasoning skills to medical students in a problem-based learning session was as effective as traditional problem-based learning sessions; however, post hoc surveys demonstrated that students were not as accepting of online learning as a teaching modality. 15 Our survey data at 6 months and 1 year combined with Web metric data suggest that the morning report blog was accessed frequently and that it was perceived as a useful educational tool.…”
Section: Discussionmentioning
confidence: 94%
“…A blog created to teach clinical reasoning skills to medical students in a problem-based learning session was as effective as traditional problem-based learning sessions; however, post hoc surveys demonstrated that students were not as accepting of online learning as a teaching modality. 15 Our survey data at 6 months and 1 year combined with Web metric data suggest that the morning report blog was accessed frequently and that it was perceived as a useful educational tool.…”
Section: Discussionmentioning
confidence: 94%
“…However, similar lack of effect for virtual or web-based problem-based learning activities on clinical reasoning skills has been previously reported, albeit in medical students. 42 The lack of randomization to the online scenarios may be considered a limitation; however, had this been adopted, it is possible that contamination of the two student cohorts would have occurred as students study alongside their peers on a daily basis.…”
Section: Discussionmentioning
confidence: 99%
“…Raupach et al 10 reported virtual collaborative learning to be as effective as problem-based learning sessions in the acquisition of reasoning skills in fourth year medical students. However, e-learning could increase the interest of medical students by maximising the use of clinical relevance 11.…”
Section: Introductionmentioning
confidence: 99%